Czechoslovak shipping in the inter-war period: The maritime transport operations of the Baťa Shoe Company, 1932–1935. (February 2015) - Herman, Jan
This article documents the Baťa Shoe Company's maritime transport operations between 1932 and 1935, a period in which the Baťa Company was engaged in 35 fields of industry, trade and services other than shoe production. The opening section focuses on the contracts that guaranteed the newly formed Czechoslovakia the right to engage in sea transport, followed by a brief description of maritime transportation developments. The core of the article deals with the efforts of the Baťa Company to operate two former naval vessels to ship its raw materials. The larger vessel, Morava, was intended to deliver goods from Europe to Southeast Asia. On the return leg, she was to haul raw material for footwear manufacturing, mainly rubber and leather. However, Morava only made one trip to Asia, and then transported goods among European ports before being sold just one year later. The smaller vessel, Little Evy, was purchased to transport freight on the Hamburg–Gdynia–Hamburg route. She did so for a year and a half before being sold after a collision, bringing to an end the new nation's most important maritime transport endeavour of the 1930s. It would be two decades after the Second World War before another naval vessel flew the Czechoslovak flag.